HUBUNGAN PENGETAHUAN INFORMASI NILAI GIZI DENGAN PERILAKU MEMBACA LABEL INFORMASI NILAI GIZI PADA MAHASISWA - Tri Zantika; Pramudya Kurnia (Poltekkes Kemenkes Pontianak, 2023)
The nutritional problem in adolescents is the lack of awareness of reading labels on nutritional value information on packaged food and drinks. The aim of the study was to analyze the relationship between knowledge about nutritional value information and reading behavior on nutritional value information labels for students of the Nutrition Science Study Program, Muhammadiyah University of Surakarta. This study used a simple random sampling method, cross sectional analysis, research using Google from. In this study, students of the Nutrition Science Study Program, University of Muhammadiyah Surakarta, were the subjects. The research data was obtained through questionnaires distributed through the Google form. The results of the research were female (95.5%) and male (4.5%) respondents, early adulthood (46.8%) and middle adulthood (53.2%), class of 2018 (52.3%) and class 2021 (47.7%), knowledge is not good (32.4%), good (67.6%) and behavior is not good (36.0%), good (64.0%), there is a relationship between knowledge and behavior between knowledge and behavior in reading nutritional value information labels, the p-value was 0.01 (P<0.05), the knowledge variable was more than half of the respondents (67.6%) had a good level of knowledge.